Penentuan Komoditas Unggulan Tanaman Pangan Berdasarkan Nilai Produksi di Kabupaten Kotawaringin Barat - Novi Nurhayati (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2016)
The purpose of this study was to determine the type of food crops which is the leading commodity in regency Kotawaringin Barat and rate of growth of food crops and contribute production of food crops against the total value of crop production. The data used is secondary data obtained from the Badan Pusat Statistik Kotawaringin Barat Regency. The period of data analyzed in this study were between 2010-2014. The method used is location quotient and analyzed klassen typology. Food crops which is the leading commodity in Kotawaringin Barat Regency is a plant rice, corn and peanuts. The structure of production growth of food crops that include advance and rapidly growing category is the rice plant; which includes fast-growing category is the peanut and soybean, which include forward and slow-growing category is the corn crop; and that includes commodities lagging behind is cassava, sweet potatoes and green beans.